2016
DOI: 10.1186/s12864-016-2882-0
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing and degradome analysis reveal altered expression of miRNAs and their targets in a male-sterile cybrid pummelo (Citrus grandis)

Abstract: BackgroundG1 + HBP is a male sterile cybrid line with nuclear genome from Hirado Buntan pummelo (C. grandis Osbeck) (HBP) and mitochondrial genome from “Guoqing No.1” (G1, Satsuma mandarin), which provides a good opportunity to study male sterility and nuclear-cytoplasmic cross talk in citrus. High-throughput sRNA and degradome sequencing were applied to identify miRNAs and their targets in G1 + HBP and its fertile type HBP during reproductive development.ResultsA total of 184 known miRNAs, 22 novel miRNAs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 65 publications
3
25
0
1
Order By: Relevance
“…1), which was compliant with many other RNA-Seq experiments (e.g. [40][41][42]) and correlated with the abundance of siRNAs and miRNAs, respectively. The unique reads were annotated against Rfam [43,44] and miRBase [45][46][47][48][49][50] databases, and from the latter both mature (named in tables as 'miRBase') and precursor sequences (named as 'Hairpin') were taken into account.…”
Section: Sequencing and Annotation Of Yellow Lupine Srnassupporting
confidence: 83%
“…1), which was compliant with many other RNA-Seq experiments (e.g. [40][41][42]) and correlated with the abundance of siRNAs and miRNAs, respectively. The unique reads were annotated against Rfam [43,44] and miRBase [45][46][47][48][49][50] databases, and from the latter both mature (named in tables as 'miRBase') and precursor sequences (named as 'Hairpin') were taken into account.…”
Section: Sequencing and Annotation Of Yellow Lupine Srnassupporting
confidence: 83%
“…EMSA analysis confirmed that DREB protein is an integral part of the transcriptional regulatory circuit. Further investigations revealed that DREBbs are abundant in many MIR167 gene promoter-regulatory sequences and also in other stress regulated miRNAs ( Figure S9), 29,30 suggesting evolutionarily conserved role of DREB in miRNA transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Go and KEGG analysis showed that genes were enriched in lignin and phenylpropanoid catabolic process. Degradome sequencing that had been successfully applied to identify miRNA targets in many plant species [49,50] were employed to verify the predication results. In degradome sequencing analysis, the majority target genes were transcription factors, containing SPL, HD-ZIP and MYB genes.…”
Section: Discussionmentioning
confidence: 99%